Exosome target cell selection and the importance of exosomal tetraspanins: a hypothesis - Rana, Sanyukta; Zöller, Margot (Biochemical Society transactions, 2011)
Exosomes are derived from limiting membranes of MVBs (multivesicular bodies). They carry and transfer selected membrane and cytoplasmic proteins, mRNA and microRNA into target cells. It is due to this shipping of information that exosomes are considered to be the most promising therapeutic tool for multiple diseases. However, whereas knowledge on the composition of exosomes is rapidly increasing, the mode of selective recruitment into exosomes as well as target cell selection is poorly understood. We suggest that at least part of this task is taken over by tetraspanins. Tetraspanins, which are involved in morphogenesis, fission and fusion processes, are enriched in exosomes, and our previous work revealed that the recruitment of distinct tetraspanins into exosomes follows very selective routes, including a rearrangement of the tetraspanin web. Furthermore, only exosomes expressing a defined set of tetraspanins and associated molecules target endothelial cells, thereby contributing to angiogenesis and vasculogenesis. On the basis of these findings we hypothesize (i) that the protein assembly of exosomes and possibly the recruitment of microRNA will be regulated to a large extent by tetraspanins and (ii) that tetraspanins account for target cell selection and the tight interaction/uptake of exosomes by the target cell. Exosomes herald an unanticipated powerful path of cell-cell communication. An answer to how exosomes collect and transfer information will allow the use of Nature's concept to cope with malfunctions.